THE INFLUENCE STUDY RESULT OF THE CIVIC EDUCATION ON THE APPLICATION OF THE VALUE CHARACTER STUDENTS IN THE CLASS XI STATE SENIOR HIGH SCHOOL - ranti febriani; Holilulloh Holilullah; Muhammad Mona Adha (Jurnal Kultur Demokrasi, 2012)
The implementation of this research was meant to explain the influence of study result of the Civic education on the application of the value character students In The Class XI State Senior High School 1 Seputih Banyak Lampung Tengah. Methods used in this research is a method of descriptive correlational. Population in this research is the students class XI Senior High School 1 Seputih Banyak Lampung Tengah academic year 2012/2013. Data collected through questionnaire in this research and documentation, the engineering data analysis using formulas correlation product moment. The result showed that there are the influence of study result of the Civic education on the application of the value character students In The Class XI In The State Senior High School 1 Seputih Banyak Lampung Tengah academic year 2012/2013. The influence of study result of the education Civic on the application of the value character of students in the school class XI was in the category of very strong. This would mean higher study result of the obtained of students in the subject Civic hence the higher education also the level of the application of the value character of a student XI in the school. Keywords: The results of study, Civic education, and the value of a character